Transformational Leadership and Affective Commitment: Individual Organizational Learning and Motivation as Mediator - Kristanto, Heru (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 16 Nomor 2 Tahun 2022, 2022)
This study examines the effect of transformational leadership on an affective commitment by mediating individual-level organizational learning and motivation. The study was conducted in one of the hospitals under Yakkum in Yogyakarta city. The results showed, that there was a direct effect of transformational leadership on affective commitment. The results also show that individual-level organizational learning and motivation as partial mediators.